WE PREFER TO WORK ABROAD THAN TO SCHOOL: THE RELATIONSHIP BETWEEN EDUCATIONAL DILEMMA AND ECONOMIC CONDITIONS OF INDONESIAN MIGRANT WORKERS FAMILIES IN PONOROGO - Sari, Novita Erliana; Djatmika, Ery Tri; Wahyono, Hari; Wardoyo, Cipto (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
This research explores various factors that influence the decision of young people in Ponorogo who prefer to work abroad as Indonesian Migrant Workers (PMI) rather than continuing their education and how the family's economic conditions influence the choice to work overseas rather than continuing their education. This research took a qualitative approach with a grounded research design conducted in Pondok Village, Babadan District, Ponorogo Regency. Data was collected by observation and interviews with informants as many as 10 PMI children with ages ranging from 6-20 years. The data was then analyzed descriptively and qualitatively. The research results show that changes in economic activities give rise to a welfare dilemma for young people in Ponorogo who want to become migrant workers rather than continue their education. These results provide valuable insight into the factors that encourage individuals to choose to work abroad rather than continue their education and provide input for better policies to support the education and economic well-being of families in the region.